ANGIOTENSIN CONVERTING ENZYME INHIBITORS AND ANGIOTENSIN RECEPTOR BLOCKERS: ISN'T IT TIME TO DRAW A LINE UNDER DISCUSSION ABOUT SUPERIORITY - S. Yu. Martsevich (Столичная издательская компания, 2015)
Comments to the paper G. Savarese et al. A Meta-Analysis Reporting Effects of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers in Patients Without Heart Failure